Perioperative antibiotherapy should replace prophylactic antibiotics in patients undergoing pancreaticoduodenectomy preceded by preoperative biliary drainage. Issue 4 (11th July 2019) - Degrandi, O.; Buscail, E.; Martellotto, S.; Gronnier, C.; Collet, D.; Adam, J.P.; Ouattara, A.; Laurent, C.; Dewitte, A.; Chiche, L.
Abstract: Background and objectives: Pancreaticoduodenectomy (PD) remains a morbid surgery. Preoperative biliary drainage (PBD) is often necessary before surgery but is associated with biliary contamination. We compared the postoperative complications of patients undergoing PBD who received the usual prophylactic antibiotics (PAs) or systematic antibiotherapy (ABT). Methods: All patients who underwent surgery between 2008 and 2017 were included. Systematic perioperative ABT with piperacillin + tazobactam (ABT group) was implemented in 2014 as the standard of care for PBD. Patients treated in the period before such implementation, during which standard cefazolin was given, served as the controls (PAs group). The primary outcomes were postoperative complications. Results: We included 122 patients with PBD who underwent surgery. There were no demographic differences between the two groups. Perioperative ABT was associated with a reduction in deep abdominal abscesses (36% vs 10%, P = .0008), respiratory tract infections (15% vs 3%; P = .02), bacteremia (41% vs 6%; P < .0001), and a shorter length of hospital stay (17 [13‐27] vs 13 [10‐14] days; P < .0001). ABT was a protective factor against the development of deep abdominal abscesses (odds ratio [OR] = 0.16; P = .001) whereas smoking (OR = 3.9) and pancreatic fistula (OR = 19.1) were risk factors. Conclusion: Systematic perioperative ABT in patients undergoing PD preceded by PBD may reduce deep surgical infections and the length of hospital stay.